Visual dan Audio Mitologi Barong Landung sebagai Tema dalam Penciptaan Tari yang Berpijak pada Gerak Tari Legong Kang Cing - I Dewa Ayu Ketut Ning Sastriyani; Ida Bagus Ketut Sudiasa; Tuteng Suwandi (Jurnal Pendidikan Tari, 2022)
Barong Landung is a mythology that is believed by the Balinese people. The mythology of Barong Landung will be represented through a dance visualization that discusses the love story of King Jayapangus, Dewi Danu and Kang Cing Wie. His dance work was created to answer the problem of the original story from most of the stories circulating among the community and to answer the problem of how to create a dance work with use the mythological theme of the Barong Landung with the aim of creating a form of footing for Legong Kang Cing Wie. The method used of this dance work is the creation method of Prof. Dr. I Wayan Dibia in his book entitled "Panca Sthiti Ngawi Sani". This dance work is packaged in a dance film video format that makes it easy for the audience to see from various points of view. This dance work will be broadcast online through the YouTube channel. This dance work uses 3 dancers who play Raja Jayapangus, Dewi Danu which also acts as Kang Cing Wie and Beautiful Women.